Effects of english subtitle on intimate speech level of Vietnamese subtitled Korean TV reality shows a case study: “Roommate” subtitled by Subteam 14 = Ảnh hưởng của bản dịch tiếng Anh đối với bản dịch tiếng Việt của lời nói thân mật trong chương trình thực tế Hàn Quốc nghiên cứu điển hình: “Roommate” dịch bởi Subteam14 - Vũ, Thị Nga (2021)
To meet Hallyu Vietnamese fans’ demand for Korean dramas and reality show, more voluntary subteams have appeared and produced Vietnamese subtitles for a huge amount of videos. Despite this fact, these subteams’ translation is out of researchers’ attention because it is considered non-professional and too complex to research on. In fact, most subteams use English subtitles available on other websites for their translation in stead of producing their translation directly from Korean. Therefore, this paper was conducted to put a step into this area to shed a light on the contemporary situation of fansubbing phenomenon in Vietnam as well as the effects of intermediary translation method. Because of time and capability limit, the research used case study as its method, focusing on Subteam14, an online subteam, and two clips which are extracted from a Korean TV reality show named “Roommate” and were subtitled by the team. By utilizing qualitative method, the researcher drew conclusions on main reasons for non-professional subtitling’s low quality seriously concerned by previous researchers. Moreover, English subtitles not only play a crucial role in helping subtitlers understand the content of the original videos but greatly affects their translation method regardless of their knowledge of the source culture and source language. English subtitles may drag subtitlers far away their initial translation method which source-culture targeted due to the gap between Korean and English languages. Besides, there is inconsistence among the subtitlers engaged in the study. To overcome these problems, amateur subtitlers are suggested to improve their language proficiency and cultural knowledge, to have closer cooperation to unify their translation method.